THE IMPLEMENTATION OF VOCABULARY JOURNAL IN ENGLISH LEARNING: A CASE STUDY AT SMP NEGERI 2 BLITAR (JOSAR (Journal of Students Academic Research), 2025)
This study aims to explore the implementation of vocabulary journals as an alternative strategy for improving vocabulary acquisition in English language learning at SMP Negeri 2 Blitar. A qualitative case study approach was employed, with a sample consisting of one English teacher and four eighth-grade students selected for interviews. Data were collected through classroom observations, semi-structured interviews, and document analysis of students' vocabulary journals. The findings indicate that vocabulary journals significantly improved students' vocabulary acquisition. 80% of the students showed substantial progress in recalling and using new vocabulary, while 10% showed moderate progress, and another 10% demonstrated minimal improvement. The discussion emphasizes that vocabulary journals, when implemented with regular teacher feedback and review sessions, are an effective tool for enhancing vocabulary learning. Based on these findings, future research could explore the integration of vocabulary journals with other language learning strategies and investigate their impact across different educational contexts and age groups.